2022
DOI: 10.1108/jaoc-11-2021-0157
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental management accounting on environmental and financial performance: empirical evidence from Bangladesh

Abstract: Purpose This study aims to investigate the impact of environmental management accounting (EMA) on manufacturing companies’ environmental and financial performance in Bangladesh. Thus, this research recognizes essential factors such as EMA, environmental performance (EP), financial performance (FP), environmental information systems (EIS), knowledge management (KM), green innovation and energy efficiency (EE). Design/methodology/approach This research uses a quantitative approach and uses 323 responses from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 81 publications
4
60
1
Order By: Relevance
“…A structural equation model (PLS-SEM) is used in this study to analyze the research hypotheses. SEM is a sophisticated multivariate analysis tool used, particularly in the management and accounting research arena, to build and extend current ideas by testing the correlations between endogenous and exogenous variables [ 89 , 90 ]. If the model involves numerous constructs and items, includes a formative construct, violates the data set's normality assumption, deals with a relatively small sample size, and the research goal is to predict the key construct, PLS-SEM has advantages for predictions.…”
Section: Discussionmentioning
confidence: 99%
“…A structural equation model (PLS-SEM) is used in this study to analyze the research hypotheses. SEM is a sophisticated multivariate analysis tool used, particularly in the management and accounting research arena, to build and extend current ideas by testing the correlations between endogenous and exogenous variables [ 89 , 90 ]. If the model involves numerous constructs and items, includes a formative construct, violates the data set's normality assumption, deals with a relatively small sample size, and the research goal is to predict the key construct, PLS-SEM has advantages for predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits of SMA adoption must also be visible if extensive use is to be encouraged. Empirical evidence abounds that SMA implementation delivers benefits, such as process improvement, cost reduction, enhanced product quality, successful strategy implementation and value creation in organizations (Sedevich-Fons, 2018;Alamri, 2019;Deb et al, 2022) Three of the five top obstacles are human barriers. Two of the three human barriers are to knowledge about SMA.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies has shown that SMA can enhance organizational competitiveness (Alamri, 2019;Deb et al, 2022). Unlike TMA systems that have internal orientation, lack goal congruence and fail to adapt performance measures to changing circumstances (Shank, 2007;Chartered Institute of Management Accountants, CIMA, 2013), SMA is future-oriented, sensitive to the external environment and emphasizes long-termism.…”
Section: Research Contextmentioning
confidence: 99%
“…As a result, EMA usage helps manufacturing firms gain certain advantages. EMA can address environmental information with ecological consequences, and it improves environmental performance (Deb et al, 2023). Specifically, EMA usage assists manufacturing firms in identifying environment‐related costs, classifying environment‐related expenditures, allocating environment‐related costs to products, and developing and using environment‐related key performance indicators (Burritt et al, 2002; Ferreira et al, 2010), thereby leading to positive results in terms of environmental performance.…”
Section: Theoretical Background Model and Hypothesis Developmentmentioning
confidence: 99%
“…Previous studies have found that environmental management accounting (EMA) is a helpful tool for manufacturing firms; with it, they can confidently manage their environmental activities and achieve environmental benefits (Appannan et al, 2023; Burritt et al, 2019; Deb et al, 2023). This means that EMA usage can optimally assist manufacturing firms in making decisions that are genuinely in line with environmental criteria to achieve their best performance (Adams & Zutshi, 2004; Pondeville et al, 2013).…”
Section: Introductionmentioning
confidence: 99%